Effect of Selected Humectants as Water Activity Modifiers on the Quality of Model Khoa System - Badola, Richa; Panjagari, Narender Raju; RRB, Singh; Singh, Ashish Kumar; Shaik, Abdul Hussain (Indian Journal of Dairy Science, 2017)
Water activity and other physical properties including moisture content and instrumental colour parameters, as well as sensory parameters were analyzed to investigate the effect of addition of humectants on model khoa system. Model khoa system was specially designed to get consistent and fast results, for selection of humectant as a hurdle for preservation of khoa based products such as khoa, burfi, peda, etc. instead of undergoing laborious manufacturing processes involved in khoa and khoa based indigenous dairy products. All the five humectants studied such as polydextrose, maltodextrin, mannitol, sorbitol and corn syrup were found to have a significant (P<0.05) effect on the physical and sensory parameters. Among all, sorbitol was found to have maximum water activity reduction (0.931 at 25Â°C) potential. Principal component analysis revealed that the first three components (PC) explained 87.57% of the relationship between the samples and the attributes studied. The cluster analysis revealed grouped the 9 studied attributes into four different clusters and it displayed low dissimilarity between mannitol and sorbitol added at 20% level as compared to rest of the treatments. Thus, it was revealed that model khoa system could be effectively used for selection of humectant as water activity modifier.